LEVERAGING AI TO REVOLUTIONIZE BUSINESS PROCESSES - Adina-Georgeta CREȚAN (Challenges of the Knowledge Society, 2025)
In an increasingly dynamic and competitive industrial environment, organizations face the challenge of maintaining decision-making autonomy while responding to increasingly complex external demands. This paper proposes an intelligent, agent-based framework to coordinate simultaneous and parallel negotiations among autonomous entities such as microgrids or organizations operating within the same sector competing for access to limited and heterogeneous resources. The model targets organizations that are unable to independently fulfill large-scale contracts and are therefore compelled to outsource parts of these contracts, sometimes even to competitors. Each organization aims to preserve its autonomy and minimize the disclosure of sensitive business information. In this context, interoperability becomes fragile, requiring constant adjustments that may conflict with existing systems and structures. To address these challenges, the paper presents a collaborative platform supported by a cloud-based infrastructure and intelligent negotiation mechanisms, where autonomous agents iteratively evaluate and adjust offers and counteroffers. The negotiation process is managed through a communication protocol that ensures transparency, flexibility, and consistency in information exchanges. By leveraging AI, the proposed system transforms how business processes are managed, delivering key benefits such as decision automation, reduced response time, enhanced collaboration, and increased sustainability within virtual enterprise networks. Negotiation thus becomes the central mechanism through which autonomous organizations reach consensus, align objectives, and co-create value in an integrated digital ecosystem.